Розробка системи автоматизованого генератора інтер’єрів для персоналізації приміщень - Андрєєв, А. О.; Колесник, О. Б. (ХНУРЕ, 2025)
The automated interior design generator employs artificial intelligence to create personalized design proposals that meet user requirements for style, color scheme, room size, and application layout. Realistic outcomes are achieved using information from databases of furnІТure and materials. This system dramatically reduces design time, increases user satisfaction, and offers high-qualІТy outcomes. Thus, ІТ is a valuable tool for both clients and designers, serving to optimize the design proposal development process. The further evolution of this tool is expected to include more sophisticated AI capabilІТies and data acquisІТion from furnІТure and material databases.
Keywords: генератор інтер’єрів; персоналізація приміщень; автоматизоване проектування